Expression of gus and gfp genes in amphidiploid spelt wheat (Triticum spelta L.) after Agrobacterium-mediated transformation - А. В. Кирієнко; М. В. Кучук; Н. Л. Щербак; М. Ф. Парій; Ю. В. Симоненко (Plant Varieties Studying and Protection)
Purpose. To study the expression of gus and gfp genes in callus explants of amphidiploid spelt wheat (Triticum spelta L.) after Agrobacterium-mediated genetic transformation.